Artificial Intelligence Based Halal Compliance Model Civil Law Perspective - Fitri Rafianti; Winda Erika; Rusli Efendi Damanik; Aswindari Harahap (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to examine and analyze the role of the